Comparative inhibition of tetrameric carbonyl reductase activity in pig heart cytosol by alkyl 4-pyridyl ketones. (June 2014) - Shimada, Hideaki; Tanigawa, Takahiro; Matayoshi, Kazunori; Katakura, Kazufumi; Babazono, Ken; Takayama, Hiroyuki; Murahashi, Tsuyoshi; Akita, Hiroyuki; Higuchi, Toshiyuki; Eto, Masashi; Imamura, Yorishige
Abstract Context and objective: The present study is to elucidate the comparative inhibition of tetrameric carbonyl reductase (TCBR) activity by alkyl 4-pyridyl ketones, and to characterize its substrate-binding domain. Materials and methods: The inhibitory effects of alkyl 4-pyridyl ketones on the stereoselective reduction of 4-benzoylpyridine (4-BP) catalyzed by TCBR were examined in the cytosolic fraction of pig heart. Results: Of alkyl 4-pyridyl ketones, 4-hexanoylpyridine, which has a straight-chain alkyl group of five carbon atoms, inhibited most potently TCBR activity and was a competitive inhibitor. Furthermore, cyclohexyl pentyl ketone, which is substituted by cyclohexyl group instead of phenyl group of hexanophenone, had much lower ability to be reduced than hexanophenone. Discussion and conclusion: These results suggest that in addition to a hydrophobic cleft corresponding to a straight-chain alkyl group of five carbon atoms, a hydrophobic pocket with affinity for an aromatic group is located in the substrate-binding domain of TCBR.